Can advanced learners of spanish achieve native-like pronunciation? A re-examination of the critical period for accent Can advanced learners of spanish achieve native-like pronunciation? A re-examination of the critical period for accent - Frank A. Morris (Ilha do Desterro, 2008)
What is the foundation for the Critical Period Hypothesis?2 For
the last thirty years, researchers have pondered whether learners of a second language can achieve native-like pronunciation. The first attempt at addressing the issue occurred in the early 1960’s. To account for the difficulty that some children had in acquiring a first or second language, the Critical Period Hypothesis was proposed (Penfield and
Roberts, 1959; Lenneberg, 1967). It was postulated that there is a neurological based critical period, which ends at the onset of puberty. But after the critical period, mastery of a first or second language is no longer possible (Lenneberg, 1967). The cause for the lack of language attainment is attributed to a loss of neural plasticity. As the brain ages, it loses its "plasticity", and thus, its ability to learn languages. It was
suggested that language learners who started to acquire a second language before the close of the critical period could achieve nativelike levels, but those who began to learn languages after the end of the critical period would not. What is the foundation for the Critical Period Hypothesis?2 For
the last thirty years, researchers have pondered whether learners of a second language can achieve native-like pronunciation. The first attempt at addressing the issue occurred in the early 1960’s. To account for the difficulty that some children had in acquiring a first or second language, the Critical Period Hypothesis was proposed (Penfield and
Roberts, 1959; Lenneberg, 1967). It was postulated that there is a neurological based critical period, which ends at the onset of puberty. But after the critical period, mastery of a first or second language is no longer possible (Lenneberg, 1967). The cause for the lack of language attainment is attributed to a loss of neural plasticity. As the brain ages, it loses its "plasticity", and thus, its ability to learn languages. It was
suggested that language learners who started to acquire a second language before the close of the critical period could achieve nativelike levels, but those who began to learn languages after the end of the critical period would not.